2023
DOI: 10.3389/fpls.2023.1275377
|View full text |Cite
|
Sign up to set email alerts
|

The low level of plastome differentiation observed in some lineages of Poales hinders molecular species identification

Katarzyna Krawczyk,
Łukasz Paukszto,
Mateusz Maździarz
et al.

Abstract: Chloroplast genomes are a source of information successfully used in various fields of plant genetics, including molecular species identification. However, recent studies indicate an extremely low level of interspecific variability in the plastomes of some taxonomic groups of plants, including the genus Stipa L., which is a representative of the grass family. In this study we aimed to analyze the level of chloroplast genome diversity within particular genera as well as the effectiveness of identifying plant sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 84 publications
0
1
0
Order By: Relevance
“…Recently, the development of methods based on molecular diagnostic characters (MDCs) comes into view; the number of observed MDCs has a particularly large impact on the efficiency of species identification [68]. We conducted an MDC analysis of five datasets (complete cp genomes, five coding genes, six noncoding regions, ycf1, and rpl32-trnL UAG ); the results revealed that B. crassipes possessed the most abundant MDCs of the Bulbophyllum species, possibly related to the insertion observed in the genome structure (Figures 1 and 6).…”
Section: Molecular Diagnostic Characters (Mdcs)mentioning
confidence: 99%
“…Recently, the development of methods based on molecular diagnostic characters (MDCs) comes into view; the number of observed MDCs has a particularly large impact on the efficiency of species identification [68]. We conducted an MDC analysis of five datasets (complete cp genomes, five coding genes, six noncoding regions, ycf1, and rpl32-trnL UAG ); the results revealed that B. crassipes possessed the most abundant MDCs of the Bulbophyllum species, possibly related to the insertion observed in the genome structure (Figures 1 and 6).…”
Section: Molecular Diagnostic Characters (Mdcs)mentioning
confidence: 99%